Reader Response Approach: Pre-service Teachers’ Perspective Towards Reading and Comparing Folktales for Enhancing Intercultural Competence - Rachmawati, Amalia; Indarti, Titik (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
Intercultural competence is needed in the global era, where people easily interact with people from other countries. This competence is also important for teachers, as they need to transfer it to their students. Folktales are literary works that can enhance intercultural competence as they reflect a particular culture. This study aims to reveal pre-service teachers’ perspectives on reading and comparing folktales from various countries to enhance their intercultural competence using reader-response theory. The qualitative design is employed in this study by analyzing pre-service narrative reflections. This study involves 20 pre-service teachers who took Prose for English Language Education class. This study found that pre-service teachers consider that they could widen their cultural knowledge by reading and comparing folktales from various countries. Participants reported gaining insights into different cultural beliefs, values, and ways of life, recognizing universal moral values embedded in folktales, and appreciating the didactic and imaginative qualities of these narratives. The comparative approach facilitated critical thinking by enabling them to identify both similarities and differences across cultures, thus deepening their intercultural understanding. Implication of this reseach,this study encourages curriculum developers and teacher educators to integrate diverse folktales into language education programs to support the goals of the emancipated curriculum, which emphasizes intercultural understanding.